Moral judgment modulation by disgust is bi-directionally moderated by individual sensitivity - Ong, How Hwee; Mullette-Gillman, O'Dhaniel A.; Kwok, Kenneth; Lim, Julian (Frontiers in Psychology, 2014)
Modern theories of moral judgment predict that both conscious reasoning and unconscious emotional influences affect the way people decide about right and wrong. In a series of experiments, we tested the effect of subliminal and conscious priming of disgust facial expressions on moral dilemmas. “Trolley-car”-type scenarios were used, with subjects rating how acceptable they found the utilitarian course of action to be. On average, subliminal priming of disgust facial expressions resulted in higher rates of utilitarian judgments compared to neutral facial expressions. Further, in replication, we found that individual change in moral acceptability ratings due to disgust priming was modulated by individual sensitivity to disgust, revealing a bi-directional function. Our second replication extended this result to show that the function held for both subliminally and consciously presented stimuli. Combined across these experiments, we show a reliable bi-directional function, with presentation of disgust expression primes to individuals with higher disgust sensitivity resulting in more utilitarian judgments (i.e., number-based) and presentations to individuals with lower sensitivity resulting in more deontological judgments (i.e., rules-based). Our results may reconcile previous conflicting reports of disgust modulation of moral judgment by modeling how individual sensitivity to disgust determines the direction and degree of this effect.